High-efficiency electrohydrogenation of nitric oxide to ammonia on a Ni2P nanoarray under ambient conditions - Mou, Ting; Liang, Jie; Ma, Ziyu; Zhang, Longcheng; Lin, Yiting; Li, Tingshuai; Liu, Qian; Luo, Yonglan; Liu, Yang; Gao, Shuyan; Zhao, Haitao; Asiri, Abdullah M; et al. (Journal of materials chemistry. A, Materials for energy and sustainability, 2021)
Electroreduction of NO to NH3 under ambient conditions mitigates the human-caused imbalance in the global nitrogen cycle and represents a sustainable and on-site alternative to the industrial Haber–Bosch process, but its efficiency is challenged by the difficulty of identifying highly active and robust electrocatalysts for the NO reduction reaction (NORR). Herein, it is reported that a Ni2P nanosheet array on carbon paper (Ni2P/CP) acts as an efficient NORR electrocatalyst toward the highly selective hydrogenation of NO to NH3. In 0.1 M HCl, the Ni2P/CP displays a large NH3 yield of 33.47 μmol h−1 cm−2 and a fairly high faradaic efficiency of up to 76.9% at −0.2 V versus the reversible hydrogen electrode, with superb electrochemical durability under the working conditions. A proof-of-concept device consisting of a Zn–NO battery with Ni2P/CP as the cathode was assembled to deliver a discharge power density of 1.53 mW cm−2 and an NH3 yield of 62.05 μg h−1 mgcat.−1. Theoretical calculations reveal that the Ni2P (111) surface effectively promotes NO adsorption and activation via an “acceptance–donation” mechanism, and the potential-determining step is the hydrogenation of *NO to *NOH. Additionally, the possible formation of the H2 and other byproducts were also investigated theoretically, and the results support the high selectivity of the NO-to-NH3 conversion process.